Social Ritual Practices as an Arena for Integration and Negotiation of Religious and Cultural Values - Afiful Ikhwan; Mujamil Qomar; Fina Kholij Zukhrufin; Anisah Triyuliasari; Ismail (International Journal of Law and Society, 2024)
This study examines the implementation of Islamic social values ​​in the Nyadran Mbah Sutononggo culture in East Java, Indonesia. The focus of the study is directed at two main aspects: the description of the Nyadran ritual procession and the implementation of Islamic social values contained therein. This study uses a qualitative method with a phenomenological design. Data collection techniques include participatory observation, unstructured interviews, and documentation. The primary data sources used are several residents of Ngreco Village, including youth, religious leaders, academics, and village elders. Data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. To ensure data validity, this study employs triangulation, encompassing credibility, transferability, dependability, and confirmability. The findings show that the Nyadran Mbah Sutononggo tradition has two implementation styles: the first is an Islamic social style characterized by the recitation of Yasin, tahlil (joint prayer), tausiyah (study of sermons), and eating together (alms); the second is a Javanese ritual style characterized by burning incense, scattering flowers, and prayers for good fortune to the ancestors. Each ritual carries a philosophical value. From an Islamic social perspective, three main dimensions are implemented: the aqidah dimension (strengthening monotheism through prayer and religious sermons), the moral dimension (silaturahmi, cooperation, and almsgiving), and the mu'amalah dimension (traditional economic activities based on mutual assistance and cooperation). This research confirms that the Nyadran tradition is not merely a traditional ritual but also a strategic means for implementing Islamic social values. However, further efforts are needed to eradicate the accompanying polytheistic practices.